FEATURES OF THE PSYCHOEMOTIONAL STATE OF INTERNALLY DISPLACED FAMILIES FROM THE WAR ZONE - Shevchenko, Rosina; Kaafarani, Abbas; Aliieva, Tetiana; Piletska, Liybomyra; Radul, Iryna; Klepar, Mariia; Popovych, Ihor (Revista Inclusiones, 2020)
The article is devoted to the issues of psycho-emotional reaction due to emergency situations. The features of the influence of the nature of emotional expression, the presence of anxiety and depression on the somatic state of children and adolescents in conditions of internally displacement from the war zone are considered. The purpose of a research is to study the impact factors of the parental model of psycho-emotional coping with stress on the somatic state of children and, as a result, the formation of disorders of the psychosomatic spectrum. To study the psycho-emotional state of parents, we used depression questionnaires, health questionnaires “PHQ-9” and “GAD-7”, and the “Multidimensional Scale of Perceived Social Support” (“MSPSS”) methodology, which made it possible to identify factors in the formation of emotional disorders. To analyze the general somatic status of children from internally displaced families and being treated in the departments of gastroenterology, the questionnaire “BFB-K” was used. The results of the research showed the presence of a relationship between the psychoemotional state of parents and children, as one of the factors in the formation of psychosomatic complaints of children and the development of somatic aggravation of the condition.